2009
DOI: 10.1148/radiol.2533090468
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Medium–enhanced Radiation Damage Caused by CT Examinations

Abstract: The highly sensitive gammaH2AX foci assay shows that CM-enhanced radiation damage incurred in peripheral lymphocytes during CT. However, it is unknown whether long-term bioeffects of low-dose ionizing radiation from CT examinations, such as cancer, are increased by using CM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
100
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(118 citation statements)
references
References 28 publications
16
100
2
Order By: Relevance
“…It can be assumed that a cause of increased DSB as a response to contrast media can be an enhanced photoelectric absorption in the iodine atoms in the medium and consecutive exposure of adjacent lymphocytes [21]. Another study cast doubt on the effect of contrast agents due to in-vitro tests.…”
Section: Review 874mentioning
confidence: 99%
“…It can be assumed that a cause of increased DSB as a response to contrast media can be an enhanced photoelectric absorption in the iodine atoms in the medium and consecutive exposure of adjacent lymphocytes [21]. Another study cast doubt on the effect of contrast agents due to in-vitro tests.…”
Section: Review 874mentioning
confidence: 99%
“…Because this technology detects single isolated DSBs in single cells, it has exceptional sensitivity and can monitor the effect of IR doses of a few mGy (20,21). Not surprisingly, γH2AX foci analysis has been applied to assess radiation doses encountered by humans during diagnostic medical procedures, such as computed tomography scanning (22)(23)(24)(25). Moreover, this technology can be applied to different tissues (26,27) and is becoming the gold standard for various biodosimetric applications (28,29).…”
Section: Significancementioning
confidence: 99%
“…Even higher doses are encountered during radiation therapy when tumor cells need to be inactivated. In contrast to these situations, radiodiagnostic investigations encompass much lower doses, with angiographic procedures and computer tomography scans representing high-dose radiodiagnostic examples in the dose range of several 10s of milligray (3)(4)(5)(6)(7). The most frequent radiodiagnostic examinations, x-ray scans, typically involve doses of less than 1 mGy.…”
mentioning
confidence: 99%
“…We and others have shown that foci arise in a 1:1 relationship to DSBs and that the kinetics of foci loss reflect repair of DSBs (16,(20)(21)(22). This technology has the sensitivity that is necessary to investigate milligray doses and can be applied to various cell types and tissue samples (4,5,(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%